Sleep apnea leading to Parkinson’s disease – an important association - Shafqat MN (Dove Medical Press, 2017)
Muhammad Nabeel Shafqat,1 Muhammad Aadil,2 Maria Shoaib3 1Department of Medicine, University of Medical Sciences “Serafin Ruiz de Zarate” Villa Clara (UCMVC), Villa Clara, Cuba; 2Department of Psychiatry, Rush University Medical Center, Chicago, IL, USA; 3Department of Medicine, Dow Medical College, Dow University of Health Sciences, Karachi, Pakistan We read with great interest the recently published article “Sleep apnea and the subsequent risk of Parkinson disease: a 3-year nationwide population-based study” by Chou et al.1 The study is a step forward in understanding the underlying pathophysiology of Parkinson’s disease, the authors have deduced sleep apnea as one of the possible risk factors. View the original paper by Chou and colleagues.